2018
DOI: 10.1108/acmm-12-2017-1867
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection performance of reinforced steel coated with paints based on waste materials

Abstract: Purpose Using organic coatings serves as a key method to protect metal structures against corrosion. Attempts have been made to improve the corrosion inhibition of the coatings using novel types of pigments. This study aims to study the application of organic coatings containing rice straw (RS) waste as anticorrosive pigment for corrosion protection of reinforced steel. The RS was used by precipitating a thin layer of ferrite pigments on its surface to improve their characteristics and corrosion resistance act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In Mohamed et al (2018) and Ahmed et al (2016), it was suggested to obtain anti-corrosive pigments by depositing a thin layer of ferrites on the surface of rice straw waste particles, which is subjected to incineration with environmental damage. Using various electrochemical methods, it was shown that the including such pigments it is possible to provide high protective ability of the coatings in relation to low carbon steel, and zinc ferrites showed the best anti-corrosive effectiveness.…”
Section: Novel Types Of Ferrite Pigmentsmentioning
confidence: 99%
“…In Mohamed et al (2018) and Ahmed et al (2016), it was suggested to obtain anti-corrosive pigments by depositing a thin layer of ferrites on the surface of rice straw waste particles, which is subjected to incineration with environmental damage. Using various electrochemical methods, it was shown that the including such pigments it is possible to provide high protective ability of the coatings in relation to low carbon steel, and zinc ferrites showed the best anti-corrosive effectiveness.…”
Section: Novel Types Of Ferrite Pigmentsmentioning
confidence: 99%
“…However, it may not be possible to eliminate defects altogether (Kumar et al , 2001; Wilmot, 2006; Ho and Rahman, 2004; Bremner et al , 2001; Bakri and Mydin, 2014; Liubin et al , 2011; Mohamed et al , 2018; Qiao et al , 2014); the remedial measures for minimizing the defects of concrete structures can be used. These are adopting appropriate design, construction, utilization and maintenance; improving quality of concrete by adopting appropriate constituents selection, mix design, compaction and curing; preventing corrosion of reinforcement by increasing depth of concrete cover, coating rebars, chloride extraction, waterproofing and patch repair and upgrading supporting ground to control foundation settlement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Paint spray coating processes with excellent material anticorrosion properties are widely used in different processes of industrial painting, including the corrosion protections of fluid transport pipelines, such as drainage pipes [1][2][3]. The objective of anticorrosion spray coating is to adhere a paint film to a metallic surface in order to protect it from possible corrosion.…”
Section: Introductionmentioning
confidence: 99%